Strategi Optimasi Teknologi Informasi dan Komunikasi dalam Mendukung Proses Digitalisasi di Balai Desa Jabung Sisir - Karim, Abdul; Rohman, Moh Kamalul; Ali, Moh Haidar; Maulana, Huda Maksum; Ramadan, M. Rizki (Universitas Nurul Jadid, 2024)
Technology plays a crucial role in enabling efficient digital public services. However, administrative and informational systems in Jabungsisir Village are inadequate due to outdated computer equipment, a lack of an official village website, underutilized ICT for virtual meetings, and the absence of cloud storage for village documents. This research aims to identify strategies for optimizing ICT to support data digitalization processes in Jabungsisir Village. Using a descriptive qualitative method, data was gathered through observations, interviews, and documentation. The study identified key solutions, including establishing a dedicated village website, implementing cloud storage for secure document handling, and training staff on effective ICT utilization for virtual meetings. These initiatives have enhanced the efficiency, accessibility, and security of administrative processes. The findings demonstrate the potential of ICT optimization to modernize village administration and serve as a model for other villages striving to digitize their operations.